Effect of ground cover management on Thysanoptera (thrips) in clementine mandarin orchards - Aguilar-Fenollosa, Ernestina; Jaques, Josep A. (2017)
Conservation biological control by means of ground cover offers an interesting alternative to chemical control. A complex of Thysanoptera (thrips) species inhabits citrus, some of which are considered pests. This study investigated the effect of ground cover management on thrips species composition, distribution, and seasonal abundance in four commercial clementine mandarin (Citrus clementina Tanaka) orchards. Three soil management systems were compared: resident vegetation, Festuca arundinacea Schreber (Poales: Poaceae), and bare soil. Cover management affected thrips species diversity and abundance. Two of the main species causing fruit damage in Spanish citrus, Frankliniella occidentalis (Pergande) and Thrips tabaci Lindeman, were abundant in the resident ground cover. However, their abundance was strongly depressed in the F. arundinacea cover. The resident vegetation cover could provide a range of suitable host plants supporting populations of potential thrips pest species beyond the citrus blooming period. The F. arundinacea cover, which hosted Poaceae-specific thrips species, could also provide alternative food sources for Phytoseiidae mites. These predatory mites could reduce populations of potential thrips and other citrus pests below economic injury level. Our results confirm the suitability of F. arundinacea as a cover crop for clementine mandarins.